Compendium of framework and quick-win strategies for age-friendly cities in Malaysia - Rashid, Kushairi; Ismail, Hafiszah; Muhammad Soffian, Nur Shaffiqa; Azman, Muhammad Azrul Azwan; Zakariya, Aifaa Nur Syahirunnisaa (2025)
Malaysia is projected to become an ageing nation by 2035, with older adults comprising 15% of the population. The rapid demographic shift allows Malaysia limited time to prepare its cities for an ageing population, underscoring the need to identify immediate needs based on the local context. Yet a structured approach to creating age-friendly urban environments remains underdeveloped. This study proposes quick-win strategies for adapting Malaysian cities for an ageing demographic. It aims to (1) examine the demographic patterns and distribution of older adults in urban centers, (2) review age-friendly city dimensions, and (3) identify key elements suited to Malaysia’s development context. Using a deductive quantitative approach, structured surveys in Larut Matang and Kinta areas with high elderly populations, highlighted 25 essential features, forming the foundation of the Malaysia Cities for Ageing Population Framework and Strategies (MCAPS). Findings offer a strategic pathway for age-friendly planning, fostering social capital and economic benefits through inclusive urban design.